Electrospun collagen–poly(L-lactic acid-co-ε-caprolactone) membranes for cartilage tissue engineering. (July 2013) - He, Xiaomin; Fu, Wei; Feng, Bei; Wang, Hao; Liu, Zhenling; Yin, Meng; Wang, Wei; Zheng, Jinghao
Aim: To study the feasibility of electrospun collagen–poly(L -lactic acid-co-ε-caprolactone) (collagen–PLCL) membranes for cartilage tissue engineering.Materials & methods: Characteristics and mechanical properties of collagen–PLCL membranes were analyzed. The cell affinity of collagen–PLCL membranes with chondrocytes was also assessed. Then, the cell–scaffold constructs were engineered with collagen–PLCL membranes seeded chondrocytes by a sandwich model. After culture for 1 week in vitro, the constructs were implanted subcutaneously into nude mice for 4, 8 and 12 weeks, followed by evaluation of the quality of neocartilage.Results: Collagen–PLCL membranes exhibited excellent balanced properties without cytotoxicity. With the extension of implantation time in vivo, the constructs revealed more cartilage-like tissue especially at 8 and 12 weeks. The Young's modulus of the constructs also significantly increased and neared that of native cartilage at 12 weeks postimplantation.Conclusion: We suggest that collagen–PLCL membranes facilitate the formation of cartilage and thus may represent a promising scaffold for cartilage tissue engineering.